2014
DOI: 10.1111/cpf.12128
|View full text |Cite
|
Sign up to set email alerts
|

Session rating of perceived exertion following resistance exercise with blood flow restriction

Abstract: Session ratings of perceived exertion (SRPE) provide a valid and reliable indicator of resistance exercise session intensity. However, there is a lack of studies on the effects of resistance exercise with blood flow restriction (BFR) on SRPE. Thus, the aim of this study is to compare the effects of resistance exercise at high intensity versus low intensity with BFR on internal training load measured by SRPE. Thirteen young (22.2 ± 3.8 years) resistance-trained men (training experience 3.2 ± 2.4 years) particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 25 publications
4
35
0
6
Order By: Relevance
“…increases in serum growth hormone, adrenaline, noradrenaline, insulin‐like growth factor, testosterone and cortisol concentrations) (Takano et al ., ; Kon et al ., ; Neto et al ., ) with BFR. It has been suggested that this accumulation of metabolic subproducts stimulates type IV fibres (nociceptors, pain receptors), leading to enhanced percepted pain (Spranger et al ., ; Vieira et al ., ). Therefore, as shown in our results and also in other studies (Rossow et al ., ; Fitschen et al ., ; Vieira et al ., ), resistance exercise with BFR increases the RPP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…increases in serum growth hormone, adrenaline, noradrenaline, insulin‐like growth factor, testosterone and cortisol concentrations) (Takano et al ., ; Kon et al ., ; Neto et al ., ) with BFR. It has been suggested that this accumulation of metabolic subproducts stimulates type IV fibres (nociceptors, pain receptors), leading to enhanced percepted pain (Spranger et al ., ; Vieira et al ., ). Therefore, as shown in our results and also in other studies (Rossow et al ., ; Fitschen et al ., ; Vieira et al ., ), resistance exercise with BFR increases the RPP.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that this accumulation of metabolic subproducts stimulates type IV fibres (nociceptors, pain receptors), leading to enhanced percepted pain (Spranger et al ., ; Vieira et al ., ). Therefore, as shown in our results and also in other studies (Rossow et al ., ; Fitschen et al ., ; Vieira et al ., ), resistance exercise with BFR increases the RPP.…”
Section: Discussionmentioning
confidence: 97%
“…This low‐pressure continuous restriction eliminates the likelihood of complete arterial occlusion and, therefore, any possibility of thrombus formation (Rossow et al., ; Loenneke et al., ). Nerve conduction velocity is likely unaffected by low‐pressure BFR (Mittal et al., ), and while tissue oxygen saturation is reduced (Downs et al., ), exercise is often reported to be more tolerable (Hollander et al., ; Loenneke et al., ; Vieira et al., ). Taken together with previous studies, in comparison with high‐pressure BFR exercise a low‐pressure continuous restriction seems preferential when using relatively wide cuffs like those of the present study given the reduced hemodynamic stress, but should not be expected to provide any lesser beneficial adaptations to muscle strength and size when undertaken across a training period (Wernbom et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the RPE increased in both protocols, and it is speculated that as the eccentric contraction generates larger muscle damage after exercise, the stress imposed on the muscles is very high which provided a significant increase in RPE. In addition, it is observed that some studies have reported the effect of RE with BFR on the RPE (32, 37-39), but none of them evaluated the effect of eccentric RE on RPE.…”
Section: Discussionmentioning
confidence: 99%